PENGARUH KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP KINERJA DENGAN RETENSI KARYAWAN SEBAGAI MEDIASI DI PT. HUTAN SAWIT LESTARI, KOTAWARINGIN TIMUR, KAL-TENG - Laden Mering; Hansly Tunjang; Rita Yuanita Toendan (Media Bina Ilmiah, 2023)
Research in the field of potential and quality human resources in the company in achieving its goals. This study aims to determine the effect of compensation, organizational culture on employee performance, and organizational culture on employee performance through retention. Research conducted at PT. Sustainable Palm Oil Forest Unit I. Encouraging employee retention so that prospective employees remain and continue to improve employee performance. This type of research is explanatory with a census sample, namely the entire population of fresh fruit bunches (FFB) harvesters at PT. Sustainable Palm Oil Forest Unit I East Kotawaringin Regency, with a questionnaire of 108 people. Data were analyzed using SEM with SmartPLS. The results of the analysis in this study prove that the effect of compensation and organizational culture on performance through employee retention is positive and significant. The results also show that compensation and organizational culture have a positive and significant effect on employee retention.